Self-Control Modulates the Behavioral Response of Interpersonal Forgiveness - Liu, Hui; Li, Haijiang (Frontiers in Psychology, 2020)
Previous studies show that forgiveness is associated with the ability of self-control. However, whether self-control can modulate interpersonal forgiveness remains unclear. In the current study, we aim to explore the relationship between self-control and the process of forgiveness using a behavioral measure of forgiveness, during which participants will distribute money between themselves and unknown others who previously treat them fairly or unfairly in an adapted decision-making task. Seventy-two participants with low or high self-control were recruited based on their scores on the self-control scale. Results showed that participants exhibited increased anger and decreased happiness after experiencing unfair treatment. Participants with high self-control distributed more money to opponents who previously treated them unfairly compared with those with low self-control, whereas no such difference was observed to opponents who previously treated them fairly between the two groups. A significantly positive correlation was also found between the forgiveness rates and participants’ self-control scores. These findings suggest that self-control modulates interpersonal forgiveness responses. Individuals with high self-control expressed more prosocial response toward people who previously offended them, which is similar to the process of forgiveness.